THE IMPACT OF DIGITAL-BASED MARKETING STRATEGIES ON GEN Z'S SHOPPING INTEREST - Figo Alimbel; Syintia Mega Putri (Universitas Nusa Cendana, 2025)
The expected contribution of this study is to address the limitations in confirming the influence of shopping interest antecedents, particularly for Generation Z. Thus, this study aims to examine the influence of social media, e-commerce and influencers on the shopping interests of Generation Z. For this reason, this study uses a quantitative design involving 100 samples selected with a purposive sampling technique, where data is collected through a questionnaire with a Google Form and distributed to Gen Z users. The respondents' responses were analysed by descriptive analysis and statistical analysis using the SEM method on WarpPLS. The results of the analysis show that social media has a positive effect on shopping interest, e-commerce has a positive effect on shopping interest, and influencers have a positive effect on Gen Z shopping interest. Keywords: Gen Z, Shopping Interests, Social Media, E-commerce, Influencers